Вы находитесь на странице: 1из 12

LINEAR HOMOGENEOUS RECURRENCE RELATIONS

Emmie Lou Javier

Let (an) be a given sequence of numbers. A recurrence relation of the form:

c0an + c1an-1 + + cran-r = 0


where the cis are constants with c0, cr 0, and 1 r n, is called an rth order linear

homogeneous recurrence relation for the


sequence (an).

For instance, the recurrence relations

an = an-1 + an-2

(2nd order) (3rd order)

an 2an-1 + 3an-2 5an-3 = 0

Replace the terms ai with xi, i = n, n-1, , n-r, we obtain the following equation in x:

c0an + c 1xn-1 + + crrxn-r = 0 c0xn + c1an-1 + + c an-r = 0


or

(1)

c0xr + c 1xr-1 + + c r-1x + cr= 0

(2)

The equation (2) is called the characteristic equation of (1). And any root of (2) is called a characteristic root of the recurrence relation (1)

I. If 1, 2, , r are distinct characteristic roots of the recurrence relation, then


a n = A 1 (1) n + A 2 (2) n + + A r (r)

where the Ais are constants, is the general solution of (1).

II. 1, 2, , r (1 k r) are distinct characteristic roots of (1) s.t. i is of multiplicity mi, i = 1, 2, , k, then the general solution of (1) is given by a n = (A 11 +A 1 2 n++A 1 m1 n m1-1)(1) n

+ (A 21 +A 22n++A 1 m2 n m2-1) (2) n


+ + (A k1 +A k 2 n++A 1 mk n mk-1) A r (r)

where the Aijs are constants.

Result I
a n = A 1 (1) n + A 2 (2) n + + A r (r) Result II a n = (A 11 +A 1 2 n++A 1 m1 n m1-1)(1) n + (A 21 +A 22n++A 1 m2 n m2-1) (2) n

+
+ (A k1 +A k 2 n++A 1 mk n mk-1) A r (r)

Example 1: Solve the recurrence relation an = an-1 + an-2 given that a0 = 1 and a1 = 1. The recurrence relation can also be written as: an - an-1 - an-2 = 0 Its characteristic equation will be x2 x 1 = 0 And its characteristic roots will be 1=
1+ 5 and 2

2 =

1 5 2

Final solution:

=
for all n 0.

From the recurrence relation we obtain the first few terms of the sequence: 1, 1, 2, 3, 5, 8, 13, 34, 55, 89, 144, The BEAUTIFUL formula above for the nth Fibonacci number is called the Binet formula.

Example 2: Solve the recurrence relation an 7an-1 + 15an-2 9an-3 = 0 given that a0 = 1, a1 = 2 and a2 = 3.

Example 3: Solve the recurrence relation an = 2(an-1 an-2) given that a0 = 1 and a1 = 0.

Vas happenin mates?! Bloody good report eh? Hope to see you soon! Bye!!!